InSAR measurements of volcano deformation on the Central American Volcanic Arc - Ebmeier, S (2012)
Satellite measurements of volcano deformation have the potential to illuminate a wide range of volcanic processes and have provided us with the first opportunity to investigate volcano deformation as an arc-scale process. This thesis presents the results of an Interferometric Synthetic Aperture Radar (InSAR) survey of the Central American Volcanic Arc between 2007 and 2010. My measurements confirm a statistically significant absence of magmatic deformation in Central America relative to other well-studied volcanic arcs. I estimate a minimum detection threshold for deformation at 20 of the arc’s 26 active volcanoes using time series analysis of interferometric phase. I find that the majority (∼80%) of literature measurements of volcano deformation made at other arcs would have been possible with the average magnitude of noise in Central American volcanoes. The absence of measurable magmatic deformation in Central America may therefore be due to factors that limit the geodetic expression of magma movement, including the deep pooling of basalts and high parental melt volatile content. The quantification of measurement uncertainty also allows me to use the lack of deformation at specific erupting volcanoes to make order of magnitude estimations of the minimum depth for magma storage that would not result in measurable deformation. I present measurements and interpretation of non-magmatic deformation associated with edifice development at two Central American volcanoes: Arenal, Costa Rica and Santiaguito, Guatemala. At Arenal, I measure apparently steady slip (∼7 cm/yr) on the volcano’s western flanks, which I attribute to gravity-driven slip on the boundary between lavas emplaced over the past 50 years and older tephras and paleosols. At Santiaguito, I demonstrate the measurement of large-scale (∼10-200 m) topographic change from a small set of large baseline interferograms. Measurements of post-2000 lava fields allow me to estimate extrusion rate, map changes to flow morphology and make simultaneous measurements of lava flow thickness and subsidence rate.